Pengembangan E-Modul “Siap” untuk Mendukung Proyek Penguatan Profil Pelajar Pancasila - Sari Mellina Tobing; Donna Avianty (STKIP Andi Matappa Pangkep, 2023)
In implementing the project to strengthen the Pancasila student profile, it is important to pay attention to the use of developing technology. One of them is by utilizing e-modules specifically designed for P5 activities. The advantage of using electronic modules is that students can learn independently and flexibly, accessible anytime, anywhere. This research develops e-modules that are systematic, interactive, applicable and productive which aim to support the implementation of the Pancasila student profile which has been implemented so far, with the development research method (developmental research). Broadly speaking, this research was carried out in five stages ADDIE: Analysis, Design, Development, Implementation, Evaluation. Based on this research activity it can be concluded that the